Al-Qur’an Liahli al-‘Uqūl fī Sūwar al-Maīn al-Khitāb: الخطاب القرآني لأهل العقول في سور المئين - II Khobir, Abdul Lathif; Tarmom, Nabil Ahmed; Suparman, Yogi; Saputra, Adha; Al-Maswari, Abdulkhaleq Obad Mohammed (Civilization Research: Journal of Islamic Studies, 2022)
This study then aims to reveal the secrets contained in the verses of the Qur'an concerning the people of minds or human beings of a sound mind, and inevitably to know the secrets of this verse we must know its meaning and then understand the meaning of the verse. So that you can later take the lessons behind the verse secrets to work with. This study takes an analytical inductive approach by tracking the words of the interpreters in their interpretation contained in the stomachs of interpretation books and related references, and then collecting them, classifying them, presenting them, and analysing them, according to the analytical interpretation. This study proved that a speech of the people of minds in the Holy Quran includes various things, the first: matters related to beliefs such as honesty by the missionaries, preference of the hereafter over the world, certainty that the Qur'an is the greatest honor over Muslims, the ugly ness of the shirk of all kinds, God's ability to manage the universe, taking the lesson in stories the destruction of previous nations, stages of human development.